Peningkatan hasil belajar matematika melalui problem-based differentiated learning dan culturally responsive teaching - Wulandari, Hesty Ummi; Arwanto, Arwanto; Nurlaela, Nurlaela (Measurement In Educational Research, 2025)
Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang bertujuan untuk meningkatkan hasil belajar matematika peserta didik dengan menerapkan problem based differentiated learning dan culturally responsive teaching berbantuan powerpoint. Penelitian ini dilaksanakan di SMP Negeri 1 Plumbon semester ganjil tahun pelajaran 2021/2022, dengan subjek penelitian adalah kelas IX B sejumlah 35 siswa. PTK ini dilaksanakan sebanyak dua siklus yang diawali dengan pra siklus, siklus I dan siklus II. Model yang digunakan dalam penelitian ini berdasarkan model penelitian Kurt Lewin, yaitu perencanaan (planning), pelaksanaan tindakan (acting), observasi (observing), refleksi (reflecting). Hasil penelitian menunjukkan bahwa rata-rata pra-siklus sampai siklus II mengalami peningkatan dari 42,9 menjadi 53,4, kemudian 85,1. Peningkatan dari pra-siklus ke siklus I dikategorikan rendah karena nilai n-gain hanya sebesar 0,24 tetapi penelitian bisa di lanjut ke siklus II. Sedangkan peningkatan siklus I ke siklus II dikategorikan tinggi karena nilai n-gain sebesar 0,72. Jadi, problem based differentiated learning dan culturally responsive teaching berbantuan powerpoint terbukti berdampak pada peningkatan hasil belajar matematika peserta didik.   Improving mathematics learning outcomes through tailored problem-based learning and culturally responsive teaching   Abstract: This study is a Classroom Action Research (CAR) aimed at improving students' mathematics learning outcomes by applying problem-based differentiated learning and culturally responsive teaching assisted by PowerPoint. This study was conducted at SMP Negeri 1 Plumbon in the odd semester of the 2021/2022 academic year, with the research subjects being 35 students in class IX B. This CAT was conducted in two cycles, beginning with a pre-cycle, cycle I, and cycle II. The model used in this study was based on Kurt Lewin's research model, namely planning, acting, observing, and reflecting. The results showed that the average score from the pre-cycle to cycle II increased from 42.9 to 53.4, then to 85.1. The increase from the pre-cycle to cycle I was categorised as low because the n-gain value was only 0.24, but the research could be continued to cycle II. Meanwhile, the increase from cycle I to cycle II was categorised as high because the n-gain value was 0.72. Thus, problem-based differentiated learning and culturally responsive teaching assisted by PowerPoint proved to have an impact on improving students' mathematics learning outcomes.